Earnings management and european regulation 1606/2002:evidence from non-financial portuguese companies listed in Euronext - Pereira, Agostinho (2018)
Background: Since 2005, Portuguese listed companies have experienced an important institutional change, the mandatory adoption of new accounting standards (IFRS/IAS). European Union Regulation 1606/2002 made compliance with IFRS mandatory for the consolidated accounts of companies with securities traded on a regulated market. Existing literature suggests that accounting standards and country-specific characteristics affect the level of earnings management. Objectives: Therefore,thepurpose ofthispaper is to analyzehow accounting standards andthemandatory adoption of IFRS/IAS affect earning management in Portuguese listed companies. Methods: In order to do this, the paper analyze the evidence of earnings management, measured through discretionary accruals, after the adoption of IAS/IFRS by non-financial listed companies on Euronext Lisbon in the period 2005–2015. The Dechow et al. (2003) econometric model will be used, and empirical results indicate that non-financial listed companies in Portuguese stock exchange in the period 2005–2015 show evidence of discretionary accruals as a proxy for earnings management. Results: Thus, the results suggest that after the adoption of IAS/IFRS there are still indications of earnings management in non-financial listed companies. Conclusions: This research will achieve two distinct contributions. First, filling a gap at the national level, given that there was no such study, that considered the analyzed period, and second, the enrichment of the literature on this subject, since it shows that in a country of continental Europe after the mandatory adoption of IFRS earning management continues to exist.